‘We do politics so we can change politics’: communication strategies and practices in the Aam Aadmi Party’s institutionalization process - Siddarth, Divya; Shanker, Roshan; Pal, Joyojeet (Information, Communication & Society, 2021)
This decade has marked a rise in social movement-originating political parties, many of which have gained considerable political power and achieved surprising electoral success. In doing so, these parties have challenged traditional definitions and conceptualizations of party institutionalization. One such party is the Aam Aadmi Party in India, formed in the wake of the massively viral 2011 India Against Corruption (IAC) movement. Through interviews and observations, as well as digital artefact analysis, we trace the process of the Aam Aadmi Party’s institutionalization through an analysis of its media and communication practices. We argue that party workers’ drive to institutionalize into a durable electoral force has pushed AAP into projecting contradictory images and embracing conflicting narratives, both online and offline. However, the durability of the party and recent electoral successes point to the ways AAP can nonetheless inform conceptions of institutionalization.